2014
DOI: 10.12693/aphyspola.125.82
|View full text |Cite
|
Sign up to set email alerts
|

Optical Characterization of (CdO)x(ZnO)1-xComposite by Spray Pyrolysis Technique

Abstract: Composite cadmium oxideszinc oxides, (CdO)x(ZnO)1−x, thin lms are grown with variable composition, x, by non-conventional spray pyrolysis technique from two separate cavities. X-ray diraction proves the formation of cadmium and zinc peroxides upon deposition. Further annealing in air causes a loss of crystallographic order in zinc oxide grains. Annealing does not aect the structure of cadmium peroxide. The optical constants are estimated by the Murmann exact equation from transmittance and reectance in the wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Mixtures of metal oxide have gained a great attention from researchers in various scientific and industrial disciplines such as physics, chemistry, and material science due to their numerous practical applications in photocatalysis, sensing, microelectronic circuit fabrication, piezoelectric devices, fuel cell and solar cell [1–6]. Further, production of nanocomposite with controllable shapes, sizes, and surface properties is important for different practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Mixtures of metal oxide have gained a great attention from researchers in various scientific and industrial disciplines such as physics, chemistry, and material science due to their numerous practical applications in photocatalysis, sensing, microelectronic circuit fabrication, piezoelectric devices, fuel cell and solar cell [1–6]. Further, production of nanocomposite with controllable shapes, sizes, and surface properties is important for different practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…CdO and ZnO are the promising candidates in group II-VI materials showing unique nonlinear optoelectronic elements in controlling optical signals in devices. Tailoring the band gap with size dependent optical properties, within the nanoregime, will be useful for fabricating efficient optical devices [4][5][6]. Nanocrystalline ZnO/CdO composites have been prepared and the optical properties have been investigated earlier [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Using the following trial wave function, the Hamiltonian is minimized and the respective energies are found with the variation of dot size. (5) with Ee and Eh are the energy eigenvalues of the single electron and hole without the interaction term between them.…”
mentioning
confidence: 99%